“Navigating chaos”: Urban, Rural, and Remote Patient Experiences in Accessing Healthcare with Indigenous and Non-Indigenous Perspectives of Living with Chronic Low Back Pain - Katie Crockett; Stacey Lovo; Alison Irvine; Catherine Trask; Sarah Oosman; Veronica McKinney; Terrence McDonald; Nazmi Sari; Rosmary Martinez-Rueda; Harini Aiyer; Bertha Carnegie; Marie Custer; et al. (Canadian Journal of Pain, 2024)
ABSTRACTBackground Healthcare access for chronic low back pain is complex and should consider not only the health system, but patient care seeking experiences as well. People who live in rural and remote communities and/or identify as being Indigenous may often encounter additional barriers to accessing care for chronic low back pain; thus, these contexts must be considered to fully understand barriers and facilitators.Aims The aim of this study was to understand care-seeking experiences of people living with chronic back pain in Saskatchewan and determine unique experiences facing urban, rural, remote, and/or Indigenous peoples.Methods Thirty-three participants with chronic low back pain completed a preliminary survey followed by individual semistructured interviews. Participants were categorized as urban, rural, or remote including Indigenous status. A qualitative interpretive research approach with inductive thematic analysis was employed.Results Three overarching themes were identified with the following subthemes: (1) healthcare access challenges: challenges to accessing care, challenges within the health system, and challenges leading to self-directed management/coping strategies; (2) healthcare access facilitators: funded care, participant education and knowledge, patient–provider communication, and care closer to home; and (3) participant recommendations for improved care provision: coordination of care, integrative and holistic care, and patient-centered care and support. Rural and remote participants highlighted travel as a main barrier. Indigenous participant experiences emphasized communication with healthcare providers and past experiences influencing desire to access care.Conclusion Participants identified a range of challenges and facilitators as well as recommendations for improving access to care for chronic low back pain, with unique barriers for rural, remote, and Indigenous participants.